Media Canva dan Hasil Belajar Informatika Siswa MTsN 1 Pasaman - Yaumil Khairiyah; Zulfani Sesmiarni; Supratman Zaki; Liza Efriyanti (Lembaga Yasin AlSys, 2026)
The use of visual-based digital learning media is a relevant approach to improving the quality of Informatics learning at the madrasah level; however, empirical studies that specifically examine the effect of Canva-based learning media on students’ learning outcomes in Informatics subjects at Islamic junior secondary schools (MTs) remain relatively limited. This study aimed to analyze the effect of Canva-based learning media on improving the learning outcomes of Grade VIII students at MTsN 1 Pasaman. A quantitative approach with a quasi-experimental design was employed, involving 60 students selected using simple random sampling and assigned to an experimental class and a control class. Data were collected using learning outcome tests in the form of pre-tests and post-tests that had been examined for validity, reliability, difficulty level, and discriminating power, and were then analyzed using normality tests, homogeneity tests, and independent samples t-tests with IBM SPSS Statistics version 27. The findings indicate a positive and significant effect of Canva-based learning media on students’ learning outcomes, as evidenced by the higher average post-test scores of the experimental class compared to the control class and the statistically significant differences based on the independent samples t-test. These results provide empirical support for the development of technology-based digital learning practices and strengthen the application of a constructivist approach in Informatics learning. The study concludes by underscoring the importance of utilizing visual–interactive learning media to enhance learning effectiveness and recommends that teachers and educational institutions integrate Canva as one of their instructional strategies. The research also opens avenues for further studies with a broader sample scope and different subject areas.